Developing Research Questions in Natural Language Processing and Software Engineering - Nakul Sharma; Prasanth Yalla (JOIV : International Journal on Informatics Visualization, 2018)
This paper endeavors to develop newer medium of developing research questions by keeping in view both fields of SE and NLP in proper perspectives. An overview of the current state of art research in SE and NLP is presented. This is done by referring to the SE Body of Knowledge (SEBOK). Analogues to SEBOK, there are no separate Body of Knowledge available for the NLP/Computational Linguistics (CL). Hence whatever falls within the category of NLP/CL was considered in framing the research categories from the NLP/CL side. The paper concludes with future scope of the research presented.